Investment determinants of perceived image of hotel industry of the Russian South regions - A. A. Ponedelnik; N. V. Sokovnina; D. A. Ruban (Новые технологии)
Perceived image of hotel industry is determined by a number of client values of service quality. It is established that in the Russian South the bigger investment flows justified to the number of accommodation facilities and number of accommodated people really improves the perceived image of the hotel industry of a region.